TOWARD AN ETHICALLY ORGANIC JURISPRUDENCE: A PARADIGMATIC RE-IMAGINING OF SOUTH AFRICAN CONSTITUTIONALISM (The Pretoria Student Law Review, 2021)
The goal of this essay will be to posit an adapted conception of jurisprudence particular to the contemporary South African context and the needs incumbent on a post-apartheid transformative society. Constitutional jurisprudence has succeeded in many endeavours since the inception of the final constitution in 1996, taking great strides in the promotion of a fair, just and equal society. Through transformative adjudication 3 in the judiciary, see the decisions of the courts in cases like Fourie4 and Grootboom5 as examples of the judiciary intervening to promote the values of the constitution in the application of the law. As well as legislative practices like the enactment of the PAJA6 and Employment Equity7 acts, which endeavour to bring the wide values set out in the constitution into the ambit of everyday legal practice.
Keywords: constitutional jurisprudence; transformative adjudication; judiciary intervening; PAJA; Employment Equity; Fourie; Grootboom